Challenges in process optimization for new feedstocks and energy sources. (8th May 2018) - Mitsos, Alexander; Asprion, Norbert; Floudas, Christodoulos A.; Bortz, Michael; Baldea, Michael; Bonvin, Dominique; Caspari, Adrian; Schäfer, Pascal
Highlights: Challenges arising from new feedstocks are discussed. The effect of renewable energy on chemical processes is very big. Stronger collaboration of academia and industry is required. Challenges in the process development workflow are discussed. Abstract: Current and future challenges of optimization in the process industry are discussed. The gap between academic research and industrial workflow is analyzed. Moreover, issues arising from the shift from conventional fossil fuels as both feedstock and energy source to nonconventional feedstocks (shale gas, tar sands, CO2 and biomass) and penetration of intermittent renewable energy are discussed. This manuscript focuses mainly on offline model-based optimization of design and operation, including the generation and selection of promising process alternatives for new feedstocks in conceptual design, multi-objective optimization, the estimation of thermodynamic parameters of new intermediates and the optimization of process operation under the volatile availability of the new feedstocks and energy sources. Moreover, a number of opportunities and needs for research and development are identified, including the simultaneous optimization of feedstocks, processes and products and a production able to process a variety of feedstocks and to utilize energy when it is cheap.